Vpliv svetlobne onesnaženosti na fenofazo olistanja - Rajh, Mojca (Revija za geografijo, 2022)
Light pollution is one of the forms of pollution triggered by man's desire to lengthen the day. Its negative effects on the environment were discovered decades ago. However, the situation in Slovenia, despite the Regulation on limit values of light pollution, is still very alarming. The main source is public lighting. Often various buildings are too much or incorrectly illuminated. The consequences of light pollution are astronomical, biological, environmental, and economic. They can influence human health as well. Based on remote sensing data, field observations and spatial analysis, it was proved that light pollution in the area of the Voglajna valley and the upper Posotelje affects the leaf-development phenophase (leafing), both at the level of the habitat formed by small wooden landscape elements, and at the species level of the common birch (Betula pendula).
Keywords: Betula pendula; light pollution; navadna breza; sij neba; skyglow; svetlobno onesnaževanje